1965
DOI: 10.1083/jcb.27.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Effect of the New Cytotoxic Antibiotic Daunomycin on Nucleic Acids and Mitotic Activity of Hela Cells

Abstract: The effect has been studied of Actinomycin D, Daunomycin (Da.), and Da. N acetyl derivative on mitotic activity and on the nucleic acid synthesis of in vitro HeLa cell cultures. The experiments were carried out by means of the radioautographic technique using stripping films. The relative uptake of thymidine-H 3 and uridine-H 3 was determined by means of the reduced silver grain count present in the nuclei of controls and treated cells. The mitotic activity and thymidine incorporation were noticeably reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…However, the mechanism by which doxorubicin induces topoisomerase II-mediated DNA DSB does not fully explain the wide spectrum of cytotoxicity that doxorubicin exhibits (5). Several other mechanisms of action have been suggested as modes of doxorubicin-induced cell death (5,6), including inhibition of DNA and RNA synthesis (7,8), production of free radicals (9), and the formation of formaldehyde-mediated doxorubicin-DNA adducts (10,11). None of these alternative modes of cell death have been previously shown to be independent of topoisomerase II-mediated cell effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism by which doxorubicin induces topoisomerase II-mediated DNA DSB does not fully explain the wide spectrum of cytotoxicity that doxorubicin exhibits (5). Several other mechanisms of action have been suggested as modes of doxorubicin-induced cell death (5,6), including inhibition of DNA and RNA synthesis (7,8), production of free radicals (9), and the formation of formaldehyde-mediated doxorubicin-DNA adducts (10,11). None of these alternative modes of cell death have been previously shown to be independent of topoisomerase II-mediated cell effects.…”
Section: Introductionmentioning
confidence: 99%
“…Di Marco et al 21) reported that the inhibitory effect of DH on nucleic acids and mitotic activity of HeLa cells was related to the binding of DH to DNA in cells. Therefore, the presence of DNA in PBS eluting solutions could have inhibited DH activity.…”
Section: Discussionmentioning
confidence: 99%
“…[5, 9]). Anthracycline compounds are planar molecules that intercalate into nucleic acid chains [10] and disrupt DNA/RNA synthesis and repair [11]. Anthracyclines disrupt DNA in part through interactions with topoisomerase, a critical enzyme for unwinding of the DNA for replication and synthesis [12].…”
Section: Anthracycline Antibiotics: a Brief Review And Update On Mechmentioning
confidence: 99%